MEDICINE OF ANCIENT ASIAN PEOPLES - Juraeva Mastura (Journal Park Publishing, 2023)
The history of medicine has a special place among other medical sciences. He studies medicine in a wider and deeper way. The progress of medicine opens its laws. It is important for future judges (doctors) to know the history of medicine is important. The history of medicine is the essence of medicine program for students to understand and study the laws of its development serves as Increases their level and level of knowledge. Students study the history of medicine and the development of human society the opinion of medical scientists who lived in different eras about medicine and get acquainted with their opinions. These thoughts and opinions are in every era has a unique concept and idea. History of medicine in general students are deeply knowledgeable in professional-aesthetic and educational-spiritual aspects plays a big role in their development as specialists.
Keywords: purification, lymphatic vessels, medicinal plants, treatment, prevention, medicinal substances.